Supplementation with Bifidobacterium breve BR03 and B632 strains improved insulin sensitivity in children and adolescents with obesity in a cross-over, randomized double-blind placebo-controlled trial. Issue 7 (July 2021) - Solito, Arianna; Bozzi Cionci, Nicole; Calgaro, Matteo; Caputo, Marina; Vannini, Lucia; Hasballa, Iderina; Archero, Francesca; Giglione, Enza; Ricotti, Roberta; Walker, Gillian Elisabeth; Petri, Antonella; Agosti, Emanuela; et al.
Summary: Background & aims: Variations in gut microbiota might impact metabolism leading to body weight excess. We assessed the impact of a probiotic supplementation in pediatric obesity on weight, metabolic alterations, selected gut microbial groups, and functionality. Methods: Cross-over, double-blind, randomized control trial (BIFI-OBESE trial; NCT03261466). 101 youths (6–18 years, Tanner stage ≥2) with obesity and insulin-resistance on diet were randomized to 2 × 10 9 CFU/AFU/day of Bifidobacterium breve BR03 (DSM 16604) and B. breve B632 (DSM 24706) (51) or placebo (50) for 8 weeks with a 4-weeks wash-out period. Results: All subjects (M/F 54/47) completed the first 8 weeks, and 82 (M/F 43/39) the last part without adverse events. Mixed-effects models revealed a carry-over effect on many variables in the entire study, narrowing the analysis to the first 8 weeks before the wash-out periods. All subjects improved metabolic parameters, and decreased weight and Escherichia coli counts. Probiotics improved insulin sensitivity at fasting (QUICKI, 0.013 CI95%0.0–0.03) and during OGTT (ISI, 0.654 CI95%-0.11–1.41). Cytokines, GLP1, and target microbial counts did not vary. Of 25 SCFAs, acetic acid and acetic acid pentyl-ester relative abundance remained stable in the probiotics, while increased in the placebo (p < 0.02). A signature of five butanoic esters identified three clusters, one of them had better glucose responses during probiotics. Conclusion: An 8 weeks treatment with B. breve BR03 and B632 had beneficial effects on insulin sensitivity in youths with obesity. Microbiota functionality could influence metabolic answers to probiotics. Long-term studies to confirm and enrich our findings are justified. Tailored probiotic treatments could be an additional strategy for obesity. Trial registration: NCT03261466.